THE IMPLEMENTATION OF ORAL PRESENTATION IN PROMOTING LEARNER AUTONOMY IN CLASS - Kayyis, Rahmatika (JURNAL SMART, 2017)
In class of Phonetic phonology, students having confusion about a huge differences of each symbol and its phoneme between Indonesia and English. Only by giving them a lecturer in each meeting would not satisfy their needs. As it simply cannot keep up with it, learners have to be able to process and investigate their curiosity on their own autonomously.Â  Oral presentation is believed as one of implementations to promote learner autonomy in University environment. 32 students in the class divided into 10 groups presented several topics about phonetic and phonology. The data were collected through observation, interview, and questionaire. Then, they were analyzed using the steps in case study research method. The finding shows that oral presentation had given them âfreedomâto discover and autonomy to do their own learning. They also given good response relating ofÂ  what they had learnt dan investigated during teaching learning in Phonetic and Phonology Class.